Role of modern teaching aids and technologies in Ophthalmic teaching - Agrawal, Ajai (Nepalese Journal of Ophthalmology, 2017)
Clinical teaching in Ophthalmology is a big challenge. In the words of a senior professor, “I still remember those days when I used to be an undergraduate student of medicine in 1964-67 and later on as a post graduate in 1968-71, there used to be a batch of twenty to twenty-five students for OPD or indoor clinics for case presentations. The case was being shown on the indirect ophthalmoscope or slitlamp or in the operation theatre. Since it was not possible that all the students could see the patients individually by torch or on slitlamp or on any other device, therefore we had to rely most of the time on the statements of our teachers.” Now the scenario has entirely changed. All the equipments are attached with electronic devices and projection on computer monitor or much higher magnification, with the help of LCD projector, to larger group of students is possible. Thus, Ophthalmic teaching has become much easier and simpler because the teachers and the students see and discuss the same things together, at the same time. There is no need of giving the false consent of understanding when one has not comprehended what is being taught.